Antimicrobial Resistance in Agri-Food Chain and Companion Animals as a Re-emerging Menace in Post-COVID Epoch: Low-and Middle-Income Countries Perspective and Mitigation Strategies - Bandyopadhyay, Samiran; Samanta, Indranil (Frontiers in Veterinary Science, 2020)
Antimicrobial resistance (AMR) leads to enormous financial losses associated with high morbidity, mortality, man day loss, hospital length of stay, health-care and social costs. In human, over prescription of antimicrobials, which is presumably higher during COVID, is identified as the major source of selection for antimicrobial resistant bacteria but use of antimicrobials in food animals, poultry, companion animals, fishes and vegetables and moreover, environmental resistance gene pool also play an important role. The possibilities of unnecessary use of antibiotics as prophylaxis during and after COVID in livestock, poultry and companion animals exist in the low-and middle-income countries. A considerable loss in gross domestic product (GDP) is also projected in low-and middle-income countries (LMICs) due to AMR by the year 2050 which is further going to be reduced due to economic slowdown in post COVID period. Veterinary hospitals dedicated to pets have cropped up especially in urban areas of LMICs where use of antimicrobials has also been increased substantially. The inevitable preventive habit grown up during COVID with the frequent use of hand sanitizer might trigger the AMR due to presence of cross-resistance with disinfectants. In LMICs, due to the rising demand of animal protein industrial food animal production (IFAP) is slowly replacing the small-scale backyard farming system. The lack of stringent regulations and monitoring increased non-therapeutic use of antimicrobials in the industrial farms where the persistence of antimicrobial resistant bacteria is associated with several factors other than antimicrobial use such as co-resistance, cross-resistance, bacterial fitness, mixing of new and old animals, vectors or reservoirs of bacterial infection. The present review describes types of antimicrobials used in agri-food chain and companion animals in LMICs with identification of the gap in data, updated categories of prevalent antimicrobial resistant bacteria, role of animal farms as reservoir of resistant bacteria and mitigation strategies with a special focus to the pivotal strategy in post COVID period.